Nonlinear Dynamics for the prediction of Statistical Distributions: An Operational Research perspective - Ferreyra, Ricardo Tomás (2013)
Fil: Ferreyra, Ricardo Tomás. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.